Work smarter not harder: mechanical work as a measure of athlete workload - Epp-Stobbe, A.; Tsai, M.-C.; Klimstra, M. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
A thorough understanding of competition workloads is necessary to optimize athlete readiness. The purpose of this study was to investigate the contribution of mechanical work within a measure of workload (session-RPE) in women`s rugby sevens. Data from 22 international athletes, participating in 103 matches were gathered, with a total of 1108 complete datasets available for analysis. GPS-monitors worn by athletes gathered data on time and speed. Overall absolute game mechanical work and session-RPE (sRPE) values were calculated. A linear mixed model evaluated the contribution of overall game work to sRPE by athlete. A strong significant association was found between sRPE and overall game work (R2conditional=69.3, p<0.01). Ultimately, the investigation demonstrated that mechanical work may be a suitable surrogate for the more holistic measure of sRPE.